Correlation between functional condition, diet, depression indices and independence of older adults participating in physical activity programs of the national sports institute of the Maule Region, Chile - Júnior, Moacyr Portes; Portes, Leslie Andrews; Hermosilla-Palma, Felipe Andrés (Global Journal of Social Sciences Studies, 2026)
This study analyzes the relationships between functional status, diet, depression, and independence in older adults participating in physical activity workshops at the National Sports Institute (IND) in the Maule Region of Chile. For five months, bi-weekly 60-minute sessions were held, focusing on functional fitness (flexibility, balance, strength, agility, gait speed, and endurance), complemented by social and recreational activities. Pre- and post-intervention assessments used tools such as BMI, waist-to-hip ratio, the Functional Fitness Battery, a food frequency questionnaire, the Geriatric Depression Scale, and the Katz Index. The main findings show significant correlations: gait speed is moderately inversely related to age, strongly inversely related to agility, moderately positively related to lower limb strength, and weakly positively related to left leg balance. Endurance shows a moderate inverse correlation with depression. Lower limb strength is moderately positively associated with gait speed and walking distance, and inversely associated with agility and waist circumference. The discussion aligns these results with the literature, highlighting gait speed as a "vital sign" for autonomy, fall prevention, and mental health. Programs that enhance strength, agility, and balance are essential to promote independence, reduce depression, and manage adiposity in an aging population.